EVALUATION OF ABORTIFACIENT ACTIVITY OF ROOT OF LAWSONIA INERMIS THROUGH INSILICO DOCKING - J, Rajeswari; S, Rani (Asian Journal of Pharmaceutical and Clinical Research, 2015)
root of L. inermis with progesterone receptor through in silico docking. Methods: The molecular docking analysis of the 41 compounds which is derived from L. inermis with the progesterone receptor was carried out using the GOLD software. Further, the plant undergoes absorption, distribution, metabolism and excretion (ADME) analysis, and pharmacokinetic parameters have been done. Results: The results showed that D-allose is having the highest binding affinity with the progesterone receptor having a GOLD score of 32.08. D-allose present in henna inhibits the activity of progesterone and induces abortion, and it also satisfies ADME parameters. Conclusion: The findings concluded that L. inermis root exhibit abortifacient activity and further studies are suggested to isolate the active principles responsible for the activity. Keywords: Lawsonia inermis, Progesterone receptor, D-Allose, Abortifacient activity, GOLD.